Strategi Peningkatan Purchase Intention dengan Diferensiasi, Diversifikasi Produk dan Positioning pada Pabrik Roti PT Ramayana Mojokerto - Sugeng Eko Yuli Waluyo; Khasbulloh Huda; Mohamad Johan Efendi; Rachmad Sholeh (Pusat Riset dan Inovasi Nasional, 2025)
This study is to measure the extent to which consumers' intention to make purchase intention or repurchase of bakery products produced by Ramayana bakery. By using three independent variables, namely differentiation, product diversification and positioning, it is expected to be able to analyze the company's ability to win the competition so that it is able to re-attract consumer interest in making repeat purchases. The sample used in this study was 100, using the accidental sampling technique which is a direct sampling technique without any planning. Instrument testing with validity and reliability tests. While hypothesis testing with t-test and F-test. To test the data in this study using the jamovi application. We found that partially the variables Differentiation (X1), Product Diversification (X2) and Positioning (X3) have a significant influence on Purchase Intention (Y). While simultaneous analysis of the influence of differentiation (X1), product diversification (X2), and positioning (X3) on purchase intention (Y) shows that these three variables collectively play a crucial role in shaping consumer purchase intention.